2022
DOI: 10.1007/s10238-022-00825-0
|View full text |Cite
|
Sign up to set email alerts
|

The latest research trends in primary biliary cholangitis: a bibliometric analysis

Abstract: Background and aims: The bibliometric analysis uses the citation count of an article to measure its impact in the scienti c community, but no study has been undertaken to determine the most in uential papers in the eld of primary biliary cholangitis (PBC). This study aimed to investigate the global research interest regarding PBC in dentistry using a bibliometric approach. Methods: We searched the Web of Science Core Collection database to nd the top 100 most cited (T100) articles focusing on PBC. The informat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The familial risk of PBC for women with one affected first-degree relative is higher than for women with no affected relatives. 1 Furthermore, the risk of PBC was found to be higher with an increasing degree of familial relationships. 19 Growing evidence has suggested that environmental factors, in combination with genetic predisposition, play an essential role in disease development.…”
Section: Pathogenesis and Geneticsmentioning
confidence: 95%
See 3 more Smart Citations
“…The familial risk of PBC for women with one affected first-degree relative is higher than for women with no affected relatives. 1 Furthermore, the risk of PBC was found to be higher with an increasing degree of familial relationships. 19 Growing evidence has suggested that environmental factors, in combination with genetic predisposition, play an essential role in disease development.…”
Section: Pathogenesis and Geneticsmentioning
confidence: 95%
“…8 PBC prevalence has also been increasing over time. 1 In Northern England, between 1987 and 1994, prevalence increased from 20 to 33 cases per 100,000 adults, and from 54 to 94 cases per 100,000 women over the age of 40. 9 In Australia, prevalence increased from 1 to 5.1 cases per 100,000 between 1991 and 2004, 10 while in Canada, prevalence increased from 10 to 22.7 cases per 100,000 between 2002 and 2009.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Bibliometric analysis enables the qualitative and quantitative profiling of publications (4) and allows researchers to identify not only the productive countries/regions, institutions, and authors but also the research focus and emerging topics within a specific field (5,6). Additionally, bibliometric analysis has been applied in research on autoimmune digestive diseases, including inflammatory bowel disease and primary biliary cholangitis (7,8). However, a bibliometric analysis of AIP has not been reported in the literature thus far.…”
Section: Introductionmentioning
confidence: 99%